2006
DOI: 10.1007/s00223-005-0184-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cementoblast Gene Expression by Inorganic Phosphate In Vitro

Abstract: Examination of mutant and knockout phenotypes with altered phosphate/pyrophosphate distribution has demonstrated that cementum, the mineralized tissue that sheathes the tooth root, is very sensitive to local levels of phosphate and pyrophosphate. The aim of this study was to examine the potential regulation of cementoblast cell behavior by inorganic phosphate (P(i)). Immortalized murine cementoblasts were treated with P(i) in vitro, and effects on gene expression (by quantitative real-time reverse-transcriptas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 54 publications
3
101
2
Order By: Relevance
“…Studies have shown that coculture of endothelial cells with chondrocytes induces both collagen type X and ALP expression, 75 as was also shown in the collagen type X staining presented in our previous study. 49 Finally, b-glycerophosphate is the source of phosphate needed to produce hydroxyapatite, [26][27][28] but we propose that in this coculture model, these phosphates are naturally provided by cartilage cells undergoing hypertrophy within the cartilage template, 76 or from the serum contained in the expansion medium. The results suggest that a direct coculture technique can obviate the need for osteogenic supplements to induce osteogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that coculture of endothelial cells with chondrocytes induces both collagen type X and ALP expression, 75 as was also shown in the collagen type X staining presented in our previous study. 49 Finally, b-glycerophosphate is the source of phosphate needed to produce hydroxyapatite, [26][27][28] but we propose that in this coculture model, these phosphates are naturally provided by cartilage cells undergoing hypertrophy within the cartilage template, 76 or from the serum contained in the expansion medium. The results suggest that a direct coculture technique can obviate the need for osteogenic supplements to induce osteogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…12,[23][24][25] It also regulates expression of genes including osteopontin and BMP-2. [26][27][28] Exposure of rat MSCs, 12,[14][15][16][17] human MSCs (hMSCs), 9,11,13 or murine osteoblasts 22,29 to dexamethasone, ascorbic acid, and b-glycerophosphate can significantly increase alkaline phosphatase (ALP) activity in vitro.…”
mentioning
confidence: 99%
“…6,7 βGP provides inorganic phosphate (Pi) that facilitates intracellular signalling molecules. [8][9][10] Since metabolites provide the phenotypic outcome of gene expression or metabolic activities of a cell, global metabolite profiling can give a rapid snapshot of the cell physiology by monitoring concentration changes of a broad range of metabolites and provide insight into relationships between genotype and phenotype. 11,12 Therefore, metabolomics has been used widely for understanding underlying molecular processes in applications for human health and disease including biomarker and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that phosphate ions promoted osteogenic differentiation of various cell types, for example osteoblasts, cementoblasts, and periodontal ligament cells. [18][19][20][21] In the present study, titanium surfaces were modified with different H 3 PO 4 concentration using low temperature treatment. No significant difference of surface roughness was noted.…”
Section: Discussionmentioning
confidence: 99%